Motherland, fatherland, homelandsexuals - Lockwood, Patricia (Penguin poets., 2014)
"A breathtaking new collection from one of today's boldest and most adventurous poets; Colloquial and incantatory, the poems in Patricia Lockwood's second collection address the most urgent questions of our time, like: what if a deer did porn? Is America going down on Canada? What happens when Niagara Falls gets drunk at a wedding? Is it legal to marry a stuffed owl exhibit? What would Walt Whitman's tit-pics look like? Why isn't anyone named Gary anymore? Did the Hatfield and McCoy babies ever fall in love? The steep tilt of Lockwood's lines sends the reader snowballing downhill, accumulating pieces of the scenery with every turn. The poems' subject is the natural world, but their images would never occur in nature. This book is serious and funny at the same time, like a big grave with a clown lying in it. "--